A Lecturer’s and Students’ Perspective toward Ethnic Snake Game in Speaking Class at Universitas Muhammadiyah Malang - Lulud Oktaviani; Elsa Marina Desiarti (TEKNOSASTIK, 2017)
In the 21st century era, technology has influenced on many aspects of life includes education. Thus, lecturers are demanded to apply it in teaching and learning process because it can help lecturers deliver the material in attractive ways to trigger the students’ enthusiasm. There were still fewer technology usage in teaching and learning in speaking class as the researchers did a preliminary study (questionnaire) in Universitas Muhammadiyah Malang (UMM). The preliminary study showed that 63% students said their lecturer never uses multimedia-based medium in teaching speaking, yet 89% students thought the usage in classroom was important. Answering the students’ need, the researchers want to use a multimedia-based medium, Ethnic Snake Game, in speaking class for Electrical Engineering students in UMM. Thus, this research belongs to descriptive research. In using this multimedia-based medium, the lecturer and students showed positive responds.